A system model to repurpose slag into alternative brick solution for low-cost housing - Qwabe, Zwakele; Daniyan, Ilesanmi Afolabi; Ramatsetse, Boitumelo; Adeodu, Adefemi (Edelweiss Applied Science and Technology, 2024)
The world’s leading producer of Platinum Group Metal is South Africa and accounts for 94 percent of world’s platinum. Platinum smelters produce around 10 525,90 tons of slag annual of which accumulates as stockpile, never utilised. More storage area is required for continuous operation of the smelters to store slag. The aim of the research is to repurpose the slag into bricks for low-cost housing. Any Logic simulation model specifically the Discrete Event Modelling (DEM) was employed for the modelling and simulation because of its capabilities compared to other models such as Flexsim, Vensim, ANSYS. The results indicate that 92 human resources are required to have functioning business that is able to manufacture and deliver bricks enough to build 326 houses per month. The operation is labour intensive to ensure more job opportunities are created and a total 368 personnel are employed permanently on all sites. The smelter potentially saves over R1,5 billion per operation and R5,6 billion across 4 sites over a decade by giving the slag away for free. The environmental pollution is improved as five heavy plant equipment is removed from the operation. The operation has potential to generate R392,2 million profit over 10-years.